Loneliness in schizophrenia: Construct clarification, measurement, and clinical relevance - Eglit, Graham M. L.; Palmer, Barton W.; Martin, A’verria S.; Tu, Xin; Jeste, Dilip V. (PloS one, 2018)
Loneliness is a highly prevalent experience in schizophrenia. Theoretical models developed in the general population propose that loneliness is tantamount to a feeling of being unsafe, is accompanied by enhanced environmental threat perception, and leads to poor physical, emotional, and cognitive functioning. Previous research has reported that loneliness is associated with poorer physical and emotional health in schizophrenia; however, few studies have directly compared loneliness and its correlates in persons with schizophrenia and non-psychiatric comparison subjects. The purpose of the current study was to evaluate similarities and differences in the construct of loneliness, the equivalency of the measurement of this construct, and similarities and differences in the pattern of external correlates of loneliness between schizophrenia and non-psychiatric comparison groups. The third version of the University of California, Los Angeles Loneliness Scale (UCLA-3) was administered to 116 individuals with schizophrenia or schizoaffective disorder and 106 non-psychiatric comparison subjects. Additional clinical and positive psychological measures were collected, as well as demographic characteristics of the two groups. Multiple groups confirmatory factor analysis revealed that the UCLA-3 was best characterized by a bifactor model in which all items loaded on a general loneliness dimension as well as one of two orthogonal method factors reflecting item wording in both groups. Furthermore, the UCLA-3 exhibited invariant measurement of these latent constructs across groups. Mean levels of loneliness were nearly a standard deviation higher in the schizophrenia group. Nonetheless, the overall pattern and strength of correlates were largely similar across groups, with loneliness being positively associated with depression, anxiety, and perceived stress, and negatively correlated with mental well-being, happiness, and resilience. Subtle differences in correlates of age, optimism, and satisfaction with life were found. Overall, loneliness appears to be distinct from other schizophrenia-related deficits and operates similarly across schizophrenia and NC groups, suggesting that theoretical models of loneliness developed in the general population may generalize to schizophrenia.